Evaluation of nitrous oxide-oxygen and triclofos sodium as conscious sedative agents - Priya Subramaniam; K L Girish Babu; Disha Lakhotia (Wolters Kluwer Medknow Publications, 2017)
Background: Conscious sedation is used in the pediatric dentistry to reduce fear and anxiety in children and promote favorable treatment outcomes. To achieve them, the primary clinical need is for a well-tolerated, effective, and expedient analgesic and sedative agent that is safe to use. Aim: The aim of the present study was to evaluate the efficacy of nitrous oxide-oxygen and triclofos sodium as conscious sedative agents in 5-10-year-old children. Methodology: Sixty children aged 5-10 years showing anxious, uncooperative, and apprehensive behavior were randomly divided and assigned into two groups (Groups A and B) such that Group A received 40% nitrous oxide-60% oxygen and Group B received triclofos sodium in the dose of 70 mg/kg body weight, given 30 min before the treatment procedure. During the whole course of sedation procedure, the response of the child was assessed using Houpt's behavior rating scale. The acceptance of route of drug administration by the patient and parent was also assessed. Data obtained were statistically evaluated using the Mann-Whitney U-test and Chi-square test. Results: Children sedated with triclofos sodium were significantly more drowsy and disoriented compared to those sedated with nitrous oxide. The overall behavior of children in both the groups was similar. Good parental acceptance was observed for both the routes of administration. Patients accepted the oral route significantly better than inhalation route. Conclusion: Both nitrous oxide-oxygen and triclofos sodium were observed to be effective sedative agents, for successful and safe use in 5-10-year-old dental patients. Patients showed a good acceptance of the oral route compared to the inhalation route for sedation.